A method for preparing polylactic acid fiber composite ES hot air nonwoven fabric by solution blowing

CN122899006APending Publication Date: 2026-10-13SUZHOU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611015145.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-07-28
Filing Date
2026-07-09
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

而对于该类材料的无纺布面料要求其具有良好的透气过滤效果,由于ES热风无纺布中纤维网排列结构的问题,导致其材料孔隙过大,透气后过滤性能较低,并且一般的单层ES纤维热风无纺布结构单一,导致其强力较差

Benefits of technology

[0027]1、本发明ES热风无纺布采用双层纤网结构,这种结构中纤维以平铺形式存在,上下层交错,在保证纤网具有更好的孔隙率的同时,大大增强了纤网的强力,并且这种结构促使液体更容易在平面流动,难以向垂直纤维的纵向流动,进而降低了液体下渗速度,在使用过程中可以更好阻隔湿气,使纤维网更加干爽透气。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122899006A_ABST
    Figure CN122899006A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of polylactic acid fiber composite hot air nonwoven fabric, which is made of ES fiber inner layer net and polylactic acid nanofiber membrane composite.The inner layer ES fiber net is divided into upper and lower two layers: the lower layer is straight laid fiber net arranged longitudinally, and the upper layer is porous fiber net arranged longitudinally cross.The polylactic acid nanofiber membrane is prepared on the surface of pretreated double-layer ES fiber net by solution blowing technology, and the film forming effect is optimized by adjusting the parameters such as blowing air pressure and nozzle distance.The polylactic acid fiber membrane has low crystallinity and similar melting point with ES fiber, and can realize fusion bonding under hot air heating, so as to refine the pore of ES fiber net and form a high-porosity stable structure.The composite nonwoven fabric has both the air permeability and filtration property of polylactic acid and the mechanical strength of ES fiber, and the skeleton structure is enhanced and stable, which is suitable for antibacterial air permeable mask and other disposable sanitary material fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a high-porosity polylactic acid fiber / ES fiber composite hot-air nonwoven fabric, belonging to the field of hot-air nonwoven fabric preparation technology. Background Technology

[0002] Polylactic acid (PLA) is an environmentally friendly fiber with a weakly acidic surface and natural antibacterial properties, making it ideal for disposable hygiene materials. However, low-density PLA has poor heat resistance, a narrow heat processing window, and is extremely sensitive to heat and temperature. It is prone to shrinkage under hot air, making it difficult to produce 100% PLA fiber hot-air nonwoven fabric. Therefore, PLA hot-air nonwoven fabric has not yet been commercially available. Due to the natural antibacterial properties of PLA fibers, it can be used in hygiene products such as masks. Nonwoven fabrics made from this material require good breathability and filtration. However, the fiber web arrangement in ES (polylactic acid) hot-air nonwoven fabric results in excessively large pores, leading to low filtration performance after air permeation. Furthermore, the simple structure of typical single-layer ES fiber hot-air nonwoven fabric results in poor strength. Therefore, how to prepare a PLA fiber hot-air nonwoven fabric with high stability, high filtration, and good breathability has become a problem that needs to be solved. Summary of the Invention

[0003] The purpose of this invention is to provide a polylactic acid fiber / ES fiber composite hot air nonwoven fabric, which has both natural antibacterial properties and good breathability.

[0004] To solve the above-mentioned technical problems, the objective of this invention is achieved as follows:

[0005] A polylactic acid fiber composite hot-air nonwoven fabric, comprising:

[0006] An inner ES fiber mesh; and

[0007] A polylactic acid nanofiber membrane prepared by solution blow spinning and hot-air bonded to the inner ES fiber web;

[0008] The inner ES fiber web comprises an upper fiber web and a lower fiber web that are stacked together; a polylactic acid nanofiber membrane is bonded to the surface of the upper fiber web;

[0009] The lower fiber web is a straight-laid fiber web, in which the fibers are mainly arranged in the same direction, serving as the skeleton support of the product.

[0010] The fibers in the upper fiber web are arranged in a cross direction with the main fibers of the lower fiber web, forming pores.

[0011] The average pore size of the upper fiber web is 65~100µm.

[0012] In the lower fiber web, the proportion of fibers arranged in the same direction is 60-75%.

[0013] The fineness of the ES fibers in the upper fiber web is 0.6-1.5 dex, and the fineness of the ES fibers in the lower fiber web is 2.5-4 dex.

[0014] The polylactic acid nanofiber membrane has an average fiber diameter of 300~600nm, and the fiber membrane covers the surface of the upper fiber network and partially permeates into its pores.

[0015] A method for preparing polylactic acid fiber composite hot-air nonwoven fabric includes the following steps:

[0016] a) Prepare a double-layer ES fiber web, the step of which includes first forming a lower layer of direct-laid fiber web, and then forming an upper layer of porous fiber web on top of it;

[0017] b) Using solution blow spinning technology, a polylactic acid nanofiber membrane is laminated onto the surface of the double-layer ES fiber web to obtain a composite fiber web;

[0018] c) The composite fiber mesh is subjected to hot air treatment to melt and bond the polylactic acid nanofiber membrane to the double-layer ES fiber mesh to form an integrated structure.

[0019] The process parameters of the solution blow spinning technology in step b) include: blow spinning air pressure of 0.05~0.12MPa; spinning solution feed rate of 0.1~0.15ml / min; distance between nozzle and ES fiber web of 40~55cm; spinning temperature of 40~50℃; and spinning ambient humidity of less than 30%.

[0020] The polylactic acid nanofiber membrane described in step b) is prepared by using a polylactic acid / N,N-dimethylformamide solution with a mass concentration of 15-20% as the spinning solution.

[0021] Between step a) and step b), there is also a step of needle punching pretreatment of the double-layer ES fiber web, with a needle punching depth of 0.4-0.8 mm and a needle punching frequency of 200-400 times / min.

[0022] The temperature of the hot air treatment in step c) is 120~130℃.

[0023] In the preparation method described above, the porosity of the nonwoven fabric obtained under different process parameters is predicted according to the following formula:

[0024]

[0025] In the formula, Z is the nozzle distance, C is the polymer concentration in the spinning solution, P is the air pressure, and P maxK1 is the upper limit of air pressure; K2 are parameters.

[0026] Compared with the prior art, the beneficial effects achieved by the present invention are as follows:

[0027] 1. The ES hot air nonwoven fabric of this invention adopts a double-layer fiber web structure. In this structure, the fibers exist in a flat form with the upper and lower layers interlaced. While ensuring that the fiber web has better porosity, it greatly enhances the strength of the fiber web. Moreover, this structure makes it easier for liquid to flow in the plane and difficult to flow in the longitudinal direction perpendicular to the fibers, thereby reducing the liquid seepage rate. During use, it can better block moisture and make the fiber web drier and more breathable.

[0028] 2. This invention uses solution blow spinning technology to composite a layer of polylactic acid nanofiber membrane onto the surface of an ES fiber web. Solution blow spinning technology uses high-speed airflow as the stretching driving force, the solvent overcomes the surface tension of the solution and evaporates, and the solute is stretched to obtain nanofibers. Compared with electrospinning, it can achieve fiber stretching and refinement without high voltage, is safe and reliable, and has low energy consumption. At the same time, it can achieve multi-needle co-spinning with little mutual interference. The spinning speed can reach tens of times that of electrospinning, which has high practical application value. It can also flexibly deposit fibers on the surface of various receiving materials, and has wide applications in the field of composite material preparation. Moreover, the composite process is simpler, the production efficiency is high, and it can be industrialized. Using solution blow spinning technology, polylactic acid fibers can be efficiently and uniformly composited onto the surface of the upper fiber web of the ES double-layer fiber web. Due to the airflow, the nano-sized polylactic acid fibers can also penetrate into the pores of the fiber web, which is convenient for subsequent highly compatible hot air bonding.

[0029] 3. This invention discovers that low-crystallinity polylactic acid (PLA) and ES hot-air materials have almost the same melting point. Under the same heat and temperature conditions, they can achieve a consistent molten state. The solution-blown PLA nanofiber membrane composited on the surface of the prepared ES double-layer fiber web melts and bonds together under the same hot-air conditions, stretching and agglomerating, forming more irregular micropores on the surface and within the pores of the fiber web. This increases the porosity of the fiber web and improves the breathability of the nonwoven fabric. Furthermore, the non-layered, highly compatible structure formed by the hot-air bonding of PLA fibers and ES fibers endows the composite nonwoven fabric with more performance advantages, further improving the natural antibacterial and acid-base properties of ordinary ES fiber hot-air nonwoven fabrics. Its high breathability and antibacterial properties make this product widely applicable in the production of multifunctional disposable hygiene masks. Attached Figure Description

[0030] Figure 1 This is a schematic diagram of the structure of the polylactic acid / ES composite hot-air nonwoven fabric prepared by the present invention.

[0031] Figure 2 SEM image of solution blown PLA nanofibers

[0032] Figure 3 This is a SEM image of the inner ES layer and the upper porous fiber mesh.

[0033] The diagram is illustrated as follows: 1- Polylactic acid nanofiber membrane; 2- Porous upper ES fiber mesh; 3- Directly laid lower ES fiber mesh. Detailed Implementation

[0034] This invention relates to a polylactic acid (PLA) fiber composite hot-air nonwoven fabric, which is composed of an inner fiber web formed by ES fibers and an outer surface layer of PLA nanofiber membrane prepared by solution blow spinning technology. The composite material is then bonded by hot air heating to obtain the PLA fiber composite hot-air nonwoven fabric. The inner ES fiber web consists of upper and lower layers. The lower layer is a straight-laid ES fiber web with fibers arranged longitudinally, while the upper layer is a porous fiber web, including longitudinally parallel and intersecting fibers and pores with an average pore size of 65-100 μm. PLA / DMF solutions of different concentrations are prepared as spinning solutions. Through solution blow spinning technology, the spinning parameters such as blowing air pressure, nozzle distance, solution propulsion rate, temperature, and humidity are controlled and optimized to produce a uniform PLA nanofiber membrane on the surface of the needle-punched double-layer ES fiber web. The low-crystallinity polylactic acid (PLA) fiber membrane obtained by blow spinning the outer layer of the composite material has almost the same melting point as the inner ES fiber web. Under hot air mixing and heating, the PLA fibers and ES fibers melt and bond together, stretching and agglomerating the large pores of the ES fiber web to form a more microporous structure. This results in a non-layered, high-porosity, stable structure where PLA and ES fibers are highly integrated, increasing the breathability and filtration performance of the nonwoven fabric. The double-layer ES fiber web acts as a skeleton. After hot air bonding of the composite PLA, the PLA fiber composite hot air nonwoven fabric has good mechanical strength. This product can be widely used in the field of disposable hygiene materials and is suitable for the production of new antibacterial and breathable mask materials.

[0035] In some specific embodiments, the technical solution of the present invention includes:

[0036] A polylactic acid fiber composite ES hot-air nonwoven fabric, characterized in that it comprises an inner fiber web formed of ES fibers and an outer polylactic acid fiber membrane;

[0037] The ES inner fiber web is divided into upper and lower layers. The lower fiber web is a straight-laid fiber web, in which the proportion of fibers arranged longitudinally is 60-75%, and the remaining fibers have an angle of 20-30° with the longitudinal direction, and the thickness is 0.6-1.4 mm.

[0038] The upper fiber web of the ES inner layer is a porous fiber web, comprising fibers and pores arranged in parallel along the longitudinal direction, with an average pore size of 75~100μm; the thickness of the upper fiber layer is 0.8~1.6mm.

[0039] A uniform polylactic acid nanofiber membrane was spun on the surface of the upper and lower double-layer ES fiber webs using solution blow spinning technology.

[0040] The fineness of the ES fibers used in the upper fiber web is 0.6~1.5 dtex; the fineness of the ES fibers used in the lower fiber web is 2.5~4 dtex.

[0041] The polylactic acid nanofiber membrane is prepared by solution blow spinning technology using a 15-20% PLA / DMF solution prepared by dissolving polylactic acid (PLA) in N,N-dimethylformamide (DMF) and stirring for 24 hours as the spinning base liquid.

[0042] The polylactic acid material is a low-crystallinity polylactic acid with suitable thermoplasticity, and its melting point is 135°C, which is the same as the melting point of the selected ES fiber material, which also has a melting point of 135°C.

[0043] The blowing parameters for preparing polylactic acid nanofiber membrane solutions are: air pressure 0.05~0.1 MPa, feed rate 0.1~0.15 ml / min, injection needle specification 21G, nozzle distance from ES fiber web 40~50 cm, spinning temperature 40~45℃, and spinning humidity below 30%.

[0044] The solution-blown polylactic acid nanofiber membrane has an average fiber diameter of 300~600nm, is uniformly distributed on the surface of the ES fiber web, and has a thickness of 0.15~0.2mm.

[0045] The method for preparing the polylactic acid fiber composite ES hot air nonwoven fabric is as follows:

[0046] First, the ES fibers are opened and randomly combed to form a lower layer of straight-laid ES fiber web;

[0047] Then, the ES fibers are opened and combed and directly formed into a web on the lower fiber web to form the upper ES fiber web, resulting in a double-layer ES fiber web; the weight of the double-layer ES fiber web is 20~30g / ㎡.

[0048] Then, the upper and lower fiber webs laid together are sent to the needle punching area for preliminary pretreatment. During the needle punching pretreatment, the preferred needle punching depth is 0.4~0.8mm, and the needle punching frequency is 200~400 times / min.

[0049] Then, the surface of the needle-punched pretreated ES double-layer fiber web is coated with a polylactic acid nanofiber membrane by solution blow spinning under the following conditions: air pressure 0.05~0.1Mpa, feed rate 0.1~0.15ml / min, injection needle specification 21G, nozzle distance from ES fiber web 40~50cm, spinning temperature 40~45℃, and spinning humidity below 30%. The fiber membrane covers the surface of the ES fiber web and permeates into the large pores of the fiber web.

[0050] Then, the polylactic acid fiber membrane composite ES double-layer fiber web is sent into an oven for hot air penetration reinforcement. The oven temperature is controlled at 120℃~130℃, and the fiber web runs at a speed of 80 meters / minute. After exiting the oven, a breathable and porous polylactic acid fiber composite ES hot air nonwoven fabric is obtained, in which the surface polylactic acid fibers and the inner double-layer ES fiber web are highly integrated and do not separate. The upper fiber web surface is porous, while the fibers in the lower fiber web are mostly arranged in a straight line.

[0051] Example 1:

[0052] Preparation of polylactic acid fiber composite ES hot air nonwoven fabric

[0053] Materials preparation:

[0054] Polylactic acid (PLA): Low crystallinity polylactic acid, melting point 135℃;

[0055] ES fiber: The fineness is 3 dtex for the lower fiber web and 0.8 dtex for the upper fiber web;

[0056] Solvent: N,N-dimethylformamide (DMF) was selected as the organic solvent for preparing the spinning solution.

[0057] Preparation of ES double-layer fiber mesh framework:

[0058] Lower layer direct-laid fiber web: Through opening and combing, the proportion of fiber web arranged longitudinally is 70%, and the remaining fibers have an angle of 25° with the longitudinal direction; the thickness is controlled at 1.2mm.

[0059] Upper porous fiber web: A web is formed on the lower direct-laid fiber web to form a porous structure with an average pore size of 80μm and a porosity of 86%; the thickness is controlled at 1.5mm.

[0060] Needle punching pretreatment: The double-layer ES fiber mesh is fed into the needle punching area; the needle punching depth is 0.6 mm and the frequency is 300 times / min.

[0061] Preparation and lamination of polylactic acid fiber membranes:

[0062] Preparation of PLA spinning solution:

[0063] Dissolve PLA in DMF at a mass ratio of 15%, stir at 60°C for 12 hours until the solution is homogeneous, then let it stand to remove bubbles before use.

[0064] Solution blow spinning is performed on the surface of an ES double-layer fiber web as the substrate:

[0065] Spinning parameters: air pressure 0.08Mpa, feed rate 0.12ml / min, 21G needle, nozzle distance from ES fiber web surface 45cm, temperature 42℃, humidity below 30%; PLA fibers are evenly blow-spun onto the surface of the needle-punched pretreated double-layer ES fiber web.

[0066] The blown PLA fiber membrane is evenly distributed on the surface of the ES fiber web with an average diameter of 500 nm, and partially penetrates into the pores of the ES fiber web.

[0067] Hot air bonding:

[0068] The composite fiber web is fed into an oven, the temperature is controlled at 125℃ and the running speed is 80 meters / minute. Under the action of hot air penetration, PLA fibers and ES fibers melt and bond together to form a stable and non-delaminated PLA / ES composite nonwoven fabric.

[0069] Final product performance testing

[0070] Air permeability: Porosity increased to 90%; Test method (GB / T42697-2023 Nonwoven fabric porosity test method): Use a fabric air permeability tester (FX3300 model), cut 3 PLA / ES composite nonwoven fabric samples with an area of ​​100 cm², equilibrate for 24 hours under temperature (20±2℃) and humidity (65±4%) before testing, clamp the samples on the tester; set the test pressure difference to 100 Pa; measure the air volume flow rate passing through the sample per unit area per unit time, in L / (m²·s).

[0071] Antibacterial activity: Antibacterial rate reaches 98%; Test method (GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles - Part 3: Shaking method"): *Escherichia coli* was selected as the bacterial strain. The bacterial solution was dropped onto the sample (bacterial solution concentration approximately 1×10⁻⁶). 5 (CFU / mL); cover with plastic film; place in a shaker and incubate for 18–24 h at 37°C and relative humidity >90%; wash and count the number of viable bacteria on the sample and compare with the blank control group.

[0072] Mechanical strength: The tensile strength is 30% higher than that of traditional single-layer ES hot-air nonwoven fabric. Specific test data are shown in Table 1: Comparison of tensile strength between polylactic acid / ES composite hot-air nonwoven fabric and traditional single-layer ES hot-air nonwoven fabric.

[0073] Table 1

[0074] Traditional single-layer ES hot air nonwoven fabric 15.4 — Polylactic acid / ES composite hot-air nonwoven fabric (this invention) 20.2 ↑ Approximately 30%

[0075] Example 2:

[0076] The specific steps for the modified production of PLA / ES composite nonwoven fabric are as follows:

[0077] Modification of ES fiber skeleton:

[0078] Compared with Example 1, the difference is that a double-layer ES fiber web is used, but the fiber arrangement ratio is adjusted. The longitudinal arrangement ratio of the lower layer straight-laid fiber web is 60%; the average pore size of the upper layer porous fiber web is adjusted to 90μm to improve airflow permeability.

[0079] To obtain better filtration performance (higher porosity, finer pore size distribution, and better fiber uniformity), the parameters for solution blow spinning of polylactic acid (PLA) fiber membranes were experimentally controlled to obtain optimized parameters; experiments were conducted by varying the PLA spinning solution concentration. Three PLA / DMF solutions with concentrations of 15%, 18%, and 20% were used; the stirring temperature was 60℃, and the stirring time was extended to 24 hours. After the solution was stirred evenly, solution blow spinning was performed.

[0080] Optimization of blow spinning parameters:

[0081] Solution blowing was carried out under different conditions of air pressure and nozzle distance, with a feed rate of 0.15 ml / min, a temperature of 45℃, and a humidity of 30%Rh.

[0082] The final blown composite films were obtained, and the changes in blown parameters and the properties of polylactic acid / ES composite nonwoven fabrics after hot air bonding are shown in Table 2:

[0083] Table 2

[0084] 15% 0.08 45 496 90.1 97.3 18.5 18% 0.12 55 352 94.2 99.1 21.8 20% 0.10 50 403 92.0 98.5 20.1

[0085] Solution blow spinning of the outer polylactic acid nanofiber membrane was carried out under optimal parameters: PLA / DMF concentration of 18%, blowing air pressure of 0.12 MPa, nozzle distance from receiving roller of 55 cm, and feed rate of 0.15 ml / min. After hot air bonding, the pore structure of the fiber composite network was refined and the number of micropores increased. The final fabric porosity reached 94%, and the air permeability was greatly improved.

[0086] Based on the above test results, this invention further constructs a model for calculating the porosity of composite nonwoven fabrics. Since the pneumatic auxiliary device and the electric field control system work together in this patent's technical solution to achieve precise control over fiber forming, deposition, and arrangement, this process inherently possesses nonlinear saturation characteristics. Therefore, a Sigmoid function is initially set for calculating porosity, with the following parameters:

[0087]

[0088] In the formula, It is a pore-forming potential index, used to reflect the inherent tendency of a system to form a high-porosity structure under the influence of process parameters. The higher the value, the greater the possibility of forming a high-porosity structure. Especially in the process control of this patent, if in the low-pressure working region, the fiber deposition structure is mainly dominated by gravity and is not sensitive to changes in pressure; while the function in the intermediate region ( The slope is at its maximum when the porosity approaches 0, reflecting a sharp increase in the sensitivity of porosity to changes in process parameters. This is the key operating range for fine-tuning the scaffold structure. Furthermore, considering that a larger working distance provides the polymer jet with a longer travel time during blown spinning, allowing it to be stretched more fully under the influence of airflow, thus facilitating the formation of finer fibers; and since polymer concentration primarily affects solution viscosity—higher concentration, higher viscosity, and stronger entanglement between molecular chains—leading to enhanced jet resistance to tensile deformation, the ratio Z / C is defined as a comprehensive factor and thus a tensile strength index.

[0089] ; These are the weighting coefficients.

[0090] The effect of air pressure (P) in the process is non-monotonic. Within a moderate range, the auxiliary airflow generates a forward drag force on the polymer jet, which helps the fibers to be further stretched and thinned. When the pressure is too high, the strong airflow will produce a significant compaction effect when impacting the already deposited fiber network, resulting in denser fiber packing and a decrease in porosity. Therefore, a quadratic polynomial is used to describe the effect of air pressure on the polymer jet. Impact:

[0091] ; and is a coefficient.

[0092] Since the porosity tends to stabilize when the air pressure reaches a certain level, this means that at the upper limit of air pressure, right The derivative is zero at the upper limit pressure, thus yielding the constraint relationship between the parameters: . This is the upper limit of air pressure; in this experiment, it is taken as 0.12 MPa. Therefore, we obtain...

[0093]

[0094] Substituting into (1), we get:

[0095]

[0096] After substituting the experimental values, we calculated that k1 = 0.000094 and k3 = 178.918635.

[0097] Group number True porosity (%) Model predictions (%) error(%) 1 90.10 90.81 0.71 2 94.20 92.93 -1.27 3 92.00 92.45 0.50

[0098] The test values ​​and model predictions obtained under other parameter conditions were substituted into the above prediction equation for verification, and the errors are as follows:

[0099] Group number Solution concentration (%) Atmospheric pressure (MPa) Distance between nozzle and receiver (cm) True porosity (%) Model predictions (%) error(%) 1 12 0.1 60 91.33 92.45 1.23 2 22 0.09 40 92.18 91.80 -0.41 3 25 0.07 50 91.27 89.37 -2.08

[0100] It is evident that this method can be applied to the calculation of the porosity of fiber membranes under different operating conditions.

[0101] Example 3

[0102] To obtain better filtration performance (higher porosity, finer pore size distribution, and better fiber uniformity), the parameters for solution blow spinning of polylactic acid (PLA) fiber membranes were experimentally controlled to obtain optimized parameters; the results of experiments with varying PLA spinning solution concentration and solution blow spinning parameters are shown in Table 3.

[0103] solution concentration PLA / DMF concentration Too low a concentration can easily break the fibers, while too high a concentration makes spraying difficult and affects fiber formation. 15%~20% air pressure blown spinning air pressure High air pressure affects fiber stretching; it helps to refine the fibers. 0.08~0.12 MPa Nozzle and receiving distance Distance affects network structure Larger spacing results in more even fiber distribution and easier formation of pores; smaller spacing leads to uneven fiber accumulation. 45~55 cm propulsion rate Solution supply rate A high speed results in coarse fibers, while a slow speed results in low efficiency. 0.1~.15 ml / min temperature Spinning temperature Influence of solvent evaporation rate and fiber curing 40~50℃ humidity Ambient humidity High humidity affects fiber quality and drying speed. <30%Rh

[0104] The technical principles of the present invention have been described above with reference to specific embodiments. These descriptions are merely for explaining the principles of the invention and should not be construed as limiting the scope of protection of the invention in any way. Based on this explanation, those skilled in the art can readily conceive of other specific embodiments of the invention without inventive effort, and these embodiments will all fall within the scope of protection of the present invention.

Claims

1. A polylactic acid fiber composite hot-air nonwoven fabric, characterized in that, include: An inner ES fiber mesh; as well as A polylactic acid nanofiber membrane prepared by solution blow spinning and hot-air bonded to the inner ES fiber web; The inner ES fiber web comprises an upper fiber web and a lower fiber web that are stacked together; a polylactic acid nanofiber membrane is bonded to the surface of the upper fiber web; The lower fiber web is a straight-laid fiber web, in which the fibers are mainly arranged in the same direction, serving as the skeleton support of the product. The fibers in the upper fiber web are arranged in a cross direction with the main fibers of the lower fiber web, forming pores.

2. The polylactic acid fiber composite hot-air nonwoven fabric according to claim 1, characterized in that, The average pore size of the upper fiber web is 65~100µm.

3. The polylactic acid fiber composite hot-air nonwoven fabric according to claim 1, characterized in that, In the lower fiber web, the proportion of fibers arranged in the same direction is 60-75%.

4. The polylactic acid fiber composite hot-air nonwoven fabric according to claim 1, characterized in that, The fineness of the ES fibers in the upper fiber web is 0.6-1.5 dtex, and the fineness of the ES fibers in the lower fiber web is 2.5-4 dtex.

5. The polylactic acid fiber composite hot-air nonwoven fabric according to claim 1, characterized in that, The polylactic acid nanofiber membrane has an average fiber diameter of 300~600nm, and the fiber membrane covers the surface of the upper fiber network and partially permeates into its pores.

6. A method for preparing polylactic acid fiber composite hot-air nonwoven fabric as described in any one of claims 1 to 5, characterized in that, Includes the following steps: a) Prepare a double-layer ES fiber web, the step of which includes first forming a lower layer of direct-laid fiber web, and then forming an upper layer of porous fiber web on top of it; b) Using solution blow spinning technology, a polylactic acid nanofiber membrane is laminated onto the surface of the double-layer ES fiber web to obtain a composite fiber web; c) The composite fiber mesh is subjected to hot air treatment to melt and bond the polylactic acid nanofiber membrane to the double-layer ES fiber mesh to form an integrated structure.

7. The method according to claim 6, characterized in that, The process parameters of the solution blow spinning technology in step b) include: blow spinning air pressure of 0.05~0.12MPa; spinning solution feed rate of 0.1~0.15ml / min; distance between nozzle and ES fiber web of 40~55cm; spinning temperature of 40~50℃; and spinning ambient humidity of less than 30%.

8. The method according to claim 6 or 7, characterized in that, The polylactic acid nanofiber membrane described in step b) is prepared by using a polylactic acid / N,N-dimethylformamide solution with a mass concentration of 15-20% as the spinning solution.

9. The method according to claim 6, characterized in that, Between steps a) and b), there is a step of needle punching pretreatment of the double-layer ES fiber web, with a needle punching depth of 0.4-0.8 mm and a needle punching frequency of 200-400 times / min; the temperature of the hot air treatment in step c) is 120-130℃.

10. The method according to claim 6, characterized in that, In the preparation method described above, the porosity of the nonwoven fabric obtained under different process parameters is predicted according to the following formula: In the formula, Z is the nozzle distance, C is the polymer concentration in the spinning solution, P is the air pressure, and P max K1 is the upper limit of air pressure; K2 are parameters.